2016
DOI: 10.18632/oncotarget.10519
|View full text |Cite
|
Sign up to set email alerts
|

The down-regulated ING5 expression in lung cancer: A potential target of gene therapy

Abstract: ING5 can interact with p53, thereby inhibiting cell growth and inducing apoptosis. We found that ING5 overexpression not only inhibited proliferation, migration, and invasion, but also induced G2 arrest, differentiation, autophagy, apoptosis, glycolysis and mitochondrial respiration in lung cancer cells. ING5 transfection up-regulated the expression of Cdc2, ATG13, ATG14, Beclin-1, LC-3B, AIF, cytochrome c, Akt1/2/3, ADFP, PFK-1 and PDPc, while down-regulated the expression of Bcl-2, XIAP, survivin,β-catenin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
28
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 30 publications
6
28
1
Order By: Relevance
“…In spite of these the correlation between ING5 and ovarian cancer still remained unclear. Various studies reported that ING5 expression was down-regulated or ING5 was a negative regulator of chemoresistance in many kinds of tumors [18, 2534]. Consistent with these results, we demonstrated that ING5 inhibited cell proliferation, promoted cell apoptosis and inhabited chemoresistance in ovarian cancer.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In spite of these the correlation between ING5 and ovarian cancer still remained unclear. Various studies reported that ING5 expression was down-regulated or ING5 was a negative regulator of chemoresistance in many kinds of tumors [18, 2534]. Consistent with these results, we demonstrated that ING5 inhibited cell proliferation, promoted cell apoptosis and inhabited chemoresistance in ovarian cancer.…”
Section: Discussionsupporting
confidence: 90%
“…ING5, one of the ING family genes and as a transcriptional co-activator, has been demonstrated to play important roles in the development of tumor [18, 2534]. Some studies reported that the decreased ING5 protein and its cytoplasmic translocation were observed in many tumors, including bladder cancer [18], lung cancer [25, 27], oral squamous cell carcinoma [28, 30], head and neck squamous cell carcinoma [31], colorectal [32], pancreatic cancer [29], gastric carcinoma [26, 33] and ameloblastoma [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reportedly, ING5 was found to repress proliferation, and elevate autophagy and apoptosis in gastric cancer cells [37]. Additionally, ING5 played a suppressive role in proliferation, migration and invasion in lung cancer [38].…”
Section: Discussionmentioning
confidence: 95%
“…Similar to SAHA treatment, ING5 overexpression was confirmed to lower cell viability, energy metabolism, migration, and invasion and to promote the apoptosis of SH-SY5Y cells, which is consistent with other reports. [41][42][43][44] Furthermore, the same regulatory effects of ING5 were observed on phenotype-related protein expression (eg, acetylhistone upregulation). ING5 can form HAT complexes and subsequently promote histone acetylation.…”
Section: Discussionmentioning
confidence: 99%